Sequence and organization of the complete mitochondrial genome of the Ussuri mamushi (Gloydius ussuriensis). (3rd July 2016) - Han, Xiaomin; Zhao, Shuai; Xu, Chunzhu
Abstract: The mitochondrial genome sequence of Ussuri mamushi is analyzed and presented publically for the first time. The genome is 17, 208 bp in length and contains 13 protein-coding genes, 2 ribosomal RNA genes, 22 transfer RNA genes and 2 control regions. The overall base composition is A (32.4%), C (28.4%), T (26.3%) and G (12.9%). The base compositions clearly presented the A-C skew, which is the most obvious in the protein-coding genes. Mitochondrial genome analyses based on MP, ML, NJ and Bayesian analyses yielded identical phylogenetic trees, indicating a close phylogenetic affinity of the 13 Crotalinae species. It appeared that no less than two major phyletic lineages were present in Crotalinae. The main clades within the Crotalinae include Protobothrops. A clade ( G. brevicaudus, G. ussuriensis, G. intermedius, and G. sahatilis ) with the Ovophis as the sister taxon to Protobothrops was supported by bootstrap values of 88%. The four Gloydius species formed a paraphyletic group with the high bootstrap value (100%) in all examinations.